Changes in glomerular filtration rate in patients with body mass index ≥35 kg/m2 treated with metabolic and bariatric surgery versus GLP‐1 agonist at 1‐year follow‐up - Diana Cristina Henao‐Carrillo; Mayra Alejandra Jurado‐Florez; Óscar Mauricio Muñoz (Wiley, 2024)
Abstract Background Metabolic and bariatric surgery (MBS) reduces glomerular hyperfiltration. The renoprotective effects of GLP‐1 analogs were derived from clinical studies in type 2 diabetes (T2D). The objective of this study was to evaluate the changes in glomerular filtration rate (GFR) over time associated with weight loss in patients with a BMI ≥ 35 kg/m2 treated with liraglutide compared with patients treated with MBS. Methods A longitudinal study derived from a retrospective cohort of patients with BMI ≥ 35 kg/m2 treated with either MBS or liraglutide 3 mg/day, with follow‐up ≥1 year. Clinical variables, baseline GFR, and 1‐year GFR were analyzed. A generalized estimating equation (GEE) model was used to compare changes in GFR between both groups while controlling for confounding variables. Results A total of 159 patients were included in the analysis. Of these, 129 patients underwent MBS (median age 60.5 years [IQR 51.8-66.6], body mass index (BMI) 40.9 kg/m2 [IQR 0.68-0.89]), and 30 patients were treated with liraglutide (median age 56 years [IQR 46-62], BMI 37.4 kg/m2 [IQR 0.69-0.93]). No difference in baseline GFR or at 12 months of follow‐up was found between the two interventions. GEE analysis revealed an increase of 0.32 mL/min/1.73 m2 per month of follow‐up. Factors associated with a greater increase in GFR were the percentage total weight loss (%TWL) (0.12 mL/min/1.73 m2, p = 0.023) and baseline GFR (0.69 mL/min/1.73 m2, p > 0.001) for both interventions, independent of a history of T2D. Conclusion In patients with BMI ≥ 35 kg/m2, changes in GFR are related to %TWL and baseline GFR, regardless of the presence of diabetes or the type of intervention used.